Analysis Of The Use Of Hashtags As A Social Movement In Determining Public Opinion On Social Media "Twitter" (Study On Hastag #Sahkanruupks) - Gina Kusniawati (TABAYYUN, 2023)
Social media is not only used as a medium for entertainment but its users use it as a medium in shaping public opinion. A medium is needed to convey opinions and also become a discussion space for communicators and communicants. Twitter is one of the social media that provides a place for its users to convey opinions, exchange ideas, discourse and attract public sympathy through the tweets feature. This research is used to describe the reality that is happening to twitter users who care about developing issues such as this sexual violence case. This is evidenced by the creation of the hashtag #SahkanRUUPKS and the accounts that tweeted through the hashtag #SahkanRUUPKS. This research uses descriptive qualitative research methods, namely exploration and clarification of a phenomenon or social reality. By using the critical discourse analysis approach of Teun A. Van Dijk model. In conclusion, there are three levels of dimensions used in showing the discourse of support for the ratification of the sexual violence elimination bill, namely macro structure, superstructure and micro structure, as well as social cognition and social context used to see the author's awareness in writing his tweets.